Criteria and technique for the selection of students for engineering-pedagogical specialties - Bakatanova, V. (Problems of Engineer-Pedagogical Education, 2018)
The increase in the efficiency of teaching students of engineering-pedagogical specialties demands optimum professional selection of the student youth of vocational educational institutions according to certain criteria. Criteria of selecting students for engineering-pedagogical specialties are considered taking into account two positions. The first position is the optimization of the selection procedure. The second position is the efficiency of application of the chosen methods and techniques. The paper defines the following criteria for selecting students for engineering-pedagogical specialties: organization, communication, academic and language skills; inclination to teaching and manual work; bio-mental characteristics; vocational qualifications; general cultural level; social activity; self-esteem; desire to be engaged in engineering and pedagogical activity; motives for engineering and pedagogical activity; values of future professional pedagogical activity. The results of the use of the developed vocational guidance techniques allow asserting that such techniques, when used by engineering-pedagogical staff of technical vocational colleges and teachers of higher education institutions that specialize in engineering and pedagogy, are a necessary condition of high-quality professional selection.